Electrode impedance dynamics in sequential cochlear implant users: insights into cochlear immunity - Flom, Logan L.; Rasche, Eva L.; Oleson, Jacob J.; Scheperle, Rachel A.; Hansen, Marlan R. (Frontiers in Immunology, 2025)
IntroductionCochlear implant outcomes can be limited due to immunologically mediated intracochlear foreign body responses, resulting in new bone growth and fibrosis. Minimal consideration has been given to the possible role of immunological memory in modulating this response in sequentially implanted patients. We hypothesize the first implant primes the contralateral ear to respond more robustly to sequential implantation, leading to earlier increases in electrode impedance.MethodsThis is a retrospective cohort analysis of clinical impedance measurements from 79 subjects with sequential bilateral implants. Raw impedance and changes in impedance were analyzed over time according to implant sequence.ResultsPaired t-tests comparing 12-month average absolute impedance between implants were statistically significant (22 electrodes, p = 0.0176; 95% confidence interval [CI] = − 731.37, − 71.84; excluding five basal electrodes, p = 0.0070; 95% CI = − 784.31, − 128.40). Linear mixed models showed significant effects at p < 0.0001, including implant sequence, time elapsed, and electrode grouping. Estimated marginal means revealed statistically significant differences in delta impedance between all combinations of basal, middle, and apical subsets. Within each subset, statistically significant differences in delta impedance by implant sequence were observed in the basal (p = 0.0136) and apical (p = 0.0067) groups. Estimated marginal slopes of delta impedance by implant sequence were also significantly different (p < 0.0001).DiscussionMore rapid increases and greater electrode impedances are consistent with a more robust immune response in the second implanted ear. Additional investigation into the effects of implant timing, electrode array type, perioperative corticosteroids, and complex impedances may further elucidate these relationships and their implications for the cochlear immune response.